Comparative effectiveness of metformin monotherapy in extended release and immediate release formulations for the treatment of type 2 diabetes in treatment‐naïve Chinese patients: Analysis of results from the CONSENT trial. Issue 4 (22nd January 2018) - Ji, Linong; Liu, Jing; Yang, Jing; Li, Yufeng; Liang, Li; Zhu, Dalong; Li, Quanmin; Ma, Tianrong; Xu, Haiyan; Yang, Yanlan; Zeng, Jiaoe; Feng, Bo; et al.
Abstract : Aims: Metformin treatment for type 2 diabetes mellitus (T2DM) can be limited by gastrointestinal (GI) adverse events (AEs), resulting in treatment discontinuation. We investigated whether once‐daily metformin extended release (XR) is superior in terms of GI tolerability, with non‐inferior efficacy, compared with thrice‐daily metformin immediate release (IR) in treatment‐naïve Chinese patients with T2DM. Materials and Methods: This prospective, open‐label, randomized, multicentre, phase IV interventional study enrolled Chinese T2DM patients to receive either metformin XR or metformin IR with a 2‐week screening period, a 16‐week treatment period and a 2‐week follow‐up period without treatment. Co‐primary endpoints were a non‐inferiority assessment of metformin XR vs metformin IR in glycated haemoglobin (HbA1c) least squares mean (LSM) change from baseline to week 16 and the superiority of GI tolerability for metformin XR vs metformin IR. Results: Overall, 532 patients were randomized to metformin IR (n = 267) or metformin XR (n = 265). The HbA1c LSM change was −1.61% and −1.58% in each group, respectively (LSM difference, 0.03; 95% confidence interval [CI], −0.10, 0.17). Incidences of drug‐related AEs were 26.5% (n = 66) in the metformin IR‐only group and 32.2% (n = 85) in the metformin XR‐only group, and GI AEs were 23.8% and 22.3% in each group, respectively (difference, −1.52; 95% CI, −8.60, 5.56). The treatment difference met the predefined non‐inferiority upper CI margin of 0.4% in HbA1c. Conclusions: Metformin XR was non‐inferior to metformin IR for the LSM change in HbA1c from baseline to week 16 and not superior to metformin IR for overall GI AE incidence during treatment of Chinese T2DM patients.